Occupational Stress Associated With Technological Diversion Among Pretrial Services Officers: A Qualitative Case Study of GPS Supervision for Intimate Partner and Domestic Violence Cases - Lawson, Spencer G. (Journal of contemporary criminal justice, 2023)
The application of global positioning system (GPS) technology as a pretrial diversion mechanism to monitor intimate partner and domestic violence (IPV/DV) cases has become increasingly common. As more jurisdictions implement GPS technology, there is a need to understand the workplace experiences of community corrections officers with this nascent supervision strategy. This qualitative case study draws upon the experiences gleaned from in-depth interviews with all the pretrial officers assigned to technology caseloads (n = 8) in a single jurisdiction to explore prevailing occupational stress themes associated with GPS supervision for IPV/DV cases as a diversion from pretrial detention. The results reinforce and extend a range of well-established stressors in the extant literature related to pretrial officers managing a GPS caseload of IPV/DV defendants. The findings highlight that pretrial officers using GPS technology are expected to serve in other unique roles (e.g., critical educator, software engineer, data collection specialist, communication expert, and victim advocate) in the course of their duties that were unanticipated sources of occupational stress. Implications for policy and practice are discussed.